Population structure of Han population in China revealed by 41 STR loci - Weiwei Wu; Deliang Chen; Yanfang Fu; Honglei Hao; Hailun Nan; Dejian Lu (Taylor & Francis Group, 2020)
Background: Currently, the Han population in China may be comprised of different genetic groups due to geographic, cultural and economic factors. Understanding population structure is very important for forensic purposes. However, knowledge of the genetic substructure within the whole Han population in China is still limited. Aim: This study is designed to ascertain the genetic structure of the Han population in China through genetic data from autosomal short tandem repeats (STRs). Subjects and methods: A set of 41 STR markers were analysed in 8725 unrelated Han Chinese males from the seven geographic regions of Northeast, North, East, Central, South, Southwest and Northwest in mainland China. Allele frequencies and F-statistics were estimated. Principal coordinate analysis (PCoA), phylogenetic analyses, analysis of molecular variance (AMOVA) and discriminant analysis of principal components (DAPC) were performed to explore the population structure. Results: Rare alleles that have not been observed in previous samples were detected. The small overall Fst values (0.0008), AMOVA and DAPC indicated that there is no population structure in Han Chinese. However, the PCoA and phylogenetic tree disclose a genetic differentiation pattern from north to south. Conclusions: There is no apparent population substructure in the Han population in China. However, genetic distances among the Han populations correlate with geographic locations.